Nitrogen-doped activated carbon from activation of polyaniline for efficient adsorption of organic pollutants - Mingzhu Guo; Linghui Kong; Mengjiao Fan; Yuewen Shao; Yuchen Jiang; Chao Li; Shu Zhang; Shuang Wang; Xun Hu (Biomass and Bioenergy, 2026)

Hypoxic Preconditioning Enhances the Hypoxia Tolerance of the Pearl Oyster Pinctada fucata martensii and Is Associated with Changes in the Intestinal Microbiota - Qin Su; Jing Huang; Chengxin Fan; Wenhao Huang; Xinyi Zhang; Liangxi Lv; Chuangye Yang; Chenyang Yue; Yuewen Deng (Fishes, 2026)
Hypoxia frequently triggers mass mortality events in pearl oysters during the summer months. Hypoxic preconditioning (HP), repeated exposure to sublethal low-oxygen conditions, has been proposed as a potential strategy to enhance stress resistance. Here, we investigated how HP affects hypoxia tolerance in the pearl oyster Pinctada fucata martensii, with emphasis on host apoptotic and immune regulation and the gut microbiota. Pearl oysters assigned to HP (experimental group, EG) and to a non-preconditioned control group (CG) were subjected to sustained hypoxic challenge (1.5 ± 0.1 mg/L DO for 15 days). HP significantly increased the expression of apoptosis- and immunity-related genes (MyD88, IκK, NF-κB) while suppressing JNK expression in gills after extended hypoxia (MyD88: EG 2.26 ± 0.65 vs. CG 0.96 ± 0.29, p

Subsurface fertilization geometry synergies enhanced grain yield, nitrogen use efficiency and reduced greenhouse gas emissions: A global meta-analysis - Yuewen Huo; Feiyu Ying; Mengyang Zhu; Zhiwei Fan; Prakash Lakshmanan; Fusuo Zhang; Wen-Feng Cong (Field Crops Research, 2026)

Characteristics of activated carbon from carbonaceous feedstocks of varied origin - Mengjiao Fan; Chao Li; Yuewen Shao; Yuchen Jiang; Lijun Zhang; Shu Zhang; Xun Hu (Journal of Environmental Chemical Engineering, 2025)

Ni- and Co-based catalysts via alloying Ni and Co with Sn species for selective conversion of vanillin through tailoring hydrogenation and deoxygenation activity - Yuewen Shao; Mingzhu Guo; Linghui Kong; Mengjiao Fan; Kai Sun; Chao Li; Lijun Zhang; Shu Zhang; Tao Wei; Xun Hu (Fuel, 2025)

Insights into selective chlorination volatilization behavior and process optimization of Cu in FexOy-Cu2O-CaCl2-SiO2 system - Hongyan Sun; Liquan Zhu; Xiaojun Hu; Zhongzi Chen; Yuewen Fan; Kuochih Chou (Journal of Environmental Chemical Engineering, 2025)

Reaction kinetics of H2O and CO2 with molten slag containing FeO for H2-CO gas production - Yuewen Fan; Yukang Zhou; Jiahe Sun; Xiaojun Hu (Fuel, 2025)

Importance of balanced distribution of metallic sites and acidic sites in Co/Ni-based catalysts for selective conversion of polycarbonate plastic into valuable chemicals - Yuewen Shao; Chengsen Song; Mengjiao Fan; Kai Sun; Guoming Gao; Chao Li; Lijun Zhang; Shu Zhang; Tao Wei; Xun Hu (Chemical Engineering Journal, 2025)

Preparation of activated carbon with recycled ZnCl2 for maximizing utilization efficiency of the activating agent and minimizing generation of liquid waste - Mengjiao Fan; Yuewen Shao; Yongqin Wang; Jing Sun; Huiru He; Yuchen Jiang; Shu Zhang; Yi Wang; Xun Hu (Chemical Engineering Journal, 2024)

Optimization of process parameters for selective chlorination and volatilization in FeO-Cu2O-CaCl2 system - Hongyan Sun; Xiaojun Hu; Yuewen Fan; Shiming Guo; Kuochih Chou (Process Safety and Environmental Protection, 2024)

Balanced anchoring sites and volatile matter in biochar render Ni/biochar with higher metal dispersion and superior activity in hydrogenation of vanillin - Mengjiao Fan; Yuewen Shao; Chao Li; Félix Mérimé Bkangmo Kontchouo; Weidong Ren; Shu Zhang; Shuang Wang; Bin Li; Xun Hu (Fuel, 2024)

A precise method to calibrate a vessel's dynamic draft based on a single GNSS antenna - Yuewen Sun; Wenyi Duan; Fanlin Yang; Xianhai Bu; Miao Fan; Dongyue Tang; Yong Ma (Ocean Engineering, 2023)

Pyrolysis of nickel salt@cellulose to prepare Ni/C catalyst with tunable hydrogenation and acid site for the selective hydrogenation of furfuryl alcohol - Mengjiao Fan; Hongli Tian; Yuewen Shao; Lijun Zhang; Shu Zhang; Guangzhi Hu; Xun Hu (Journal of Environmental Chemical Engineering, 2023)

Cloning and promoter activity of rat Smad1 5′-flanking region in rat hepatic stellate cells - Yu Sun; Jianghong Fan; Hong Shen; Ping Li; Peter Cattini; Yuewen Gong (Molecular and Cellular Biochemistry, 2007)